(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
هدفت الدراسة الحالية لمقارنة النسيج الطلائي في الطبقة المخاطية لأجزاء جهاز الهضم عند ثلاثة أنواع من الفقاريات الدنيا: القرش Scyliorhinus caniculaوالقجاج Sparus aurata, والسلمندر Salamandra infraimmaculata . أظهرت نتائج الدراسة النسيجية والمقارنة أن معظم أجزاء جهاز الهضم للأنواع المدروسة مبطنة بنسيج طلائي بسيط في حين أن بعضها الآخر مبطن بنسيج طلائي مطبق كاذب. كما لوحظ وجود خلايا غوبلت(الخلايا الكأسية) في جميع الأجزاء المدروسة وزيادة عددها في بعض أجزاء جهاز الهضم وفقا للنوع المدروس . وتميز المري ببطانة من نسيج طلائي عمودي مهدب ، كما لوحظ وجود غدد انبوبية في ظهارة المعدة. أما الصفيحة الخاصة فكانت واضحة في كل أجزاء الجهاز الهضمي مع وجود فروقات بسيطة بحسب نوع الحيوان المدروس. The present study aimed to compare the epithelium tissue of mucosa layer of gastrointestinal tract in three types of lower vertebrates: Scyliorhinus canicula, Sparus aurata, Salamandra infraimmaculata. The results of the histological and comparative study showed that the majority of digestion system parts were lined with simple epithelium tissue while others were lined by pseudostratified epithelium tissue. Goblet cells were distributed in all studied parts of digestion systems with density in some locations. Esophagus was characterized by ciliated epithelium tissue, and the tubular glands were presents in the stomach mucosa. Concerning the Lumina properia, it was visible in all digestive system parts with some differences according to the animal species studied.